The Influence of Compensation, Job Satisfaction and Motivation on Organizational Citizenship Behavior (OCB) at PT. Pabrik Kertas Tjiwi Kimia Tbk. - Asrizal, Asrizal; Santoso, Jeffri Wahyu; Sopiah, Sopiah (Journal of Applied Business, Taxation and Economics Research, 2025)
This study aims to examine the impact of compensation, job satisfaction, and motivation on organizational citizenship behavior (OCB) of employees of PT. Pabrik Kertas Tjiwi Kimia Tbk. A quantitative approach with data collection through distributing questionnaires to predetermined respondents is used in this research method. Multiple linear regression analysis technique is a technique used to test the effect of each independent variable on the dependent variable. The results of the study indicate that compensation, job satisfaction, and motivation simultaneously and partially have a significant effect on employee OCB. This finding implies that improving these aspects can encourage voluntary work behavior that exceeds employee formal duties, which ultimately supports overall organizational performance.